Income inequality and health: New evidence from panel data - Dierk Herzer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2011)
This paper argues that previous cross-country (panel) studies on the relationship between income inequality and health suffer from significant biases due to (i) omitted country-specific factors, (ii) endogeneity, and (iii) cross-country heterogeneity in the impact of inequality on health. Using panel cointegration techniques that are robust to omitted variables, endogenous regressors, and slope heterogeneity, we find that income inequality has, on average, a small, but robust and statistically significant positive impact on population health. Also, there is some evidence that inequality is endogenous in the sense that poor health leads to increased income inequality. Finally, we find that there are large cross-country differences in the effect of income inequality on health (in about 35 percent of the cases, the effect is negative).
Keywords: I14; C23; 330; health; inequality; panel cointegration